Incidence of end-stage renal disease in the Turkish-Cypriot population of Northern Cyprus: a population based study. - Thomas M F Connor; D Deren Oygar; Daniel P Gale; Retha Steenkamp; Dorothea Nitsch; Guy H Neild; Patrick H Maxwell (PLoS ONE)
Background This is the first report of the incidence and causes of end-stage renal disease (ESRD) of the Turkish-Cypriot population in Northern Cyprus. Methods Data were collected over eight consecutive years (2004-2011) from all those starting renal replacement therapy (RRT) in this population. Crude and age-standardised incidence at 90 days was calculated and comparisons made with other national registries. We collected DNA from the entire prevalent population. As an initial experiment we looked for two genetic causes of ESRD that have been reported in Greek Cypriots. Results Crude and age-standardised incidence at 90 days was 234 and 327 per million population (pmp) per year, respectively. The mean age was 63, and 62% were male. The age-adjusted prevalence of RRT in Turkish-Cypriots was 1543 pmp on 01/01/2011. The incidence of RRT is higher than other countries reporting to the European Renal Association - European Dialysis and Transplant Association, with the exception of Turkey. Diabetes is a major cause of ESRD in those under 65, accounting for 36% of incident cases followed by 30% with uncertain aetiology. 18% of the incident population had a family history of ESRD. We identified two families with thin basement membrane nephropathy caused by a mutation in COL4A3, but no new cases of CFHR5 nephropathy. Conclusions This study provides the first estimate of RRT incidence in the Turkish-Cypriot population, describes the contribution of different underlying diagnoses to ESRD, and provides a basis for healthcare policy planning.